Peningkatan Keterampilan Berpikir Kritis dan Sikap Peduli Lingkungan Melalui Model Problem Based Learning Berbasis Literasi - Dyah Pramesti Fauzia; Badarudin Badarudin (Peneliti.net, 2022)
This guideline is a new format for template article which will be published, starting from April 2021 by Jurnal Elementaria Edukasia. Abstract is a summary of the article. Abstract must include at least: research aim, research method, and results. Abstract should stand alone, means that no citation in abstract. Consider it as the advertisement of your article. Abstract should tell the prospective reader what you did and highlight the key findings. Avoid using technical jargon and uncommon abbreviations. You must be accurate, brief, clear and specific. Use words which reflect the precise meaning. Abstract should be precise and honest. Please follow word limitations no more than 200 words. Lines are one spaced. In addition, Keywords are the labels of your manuscript and critical to correct indexing and searching. Therefore, the keywords should represent the content and highlight of your article. Use only those abbreviations that are firmly established in the field. e.g. RME. Provide at least three keywords.